Fluorescence Spectroscopic Studies of in vitro Interactions of Famotidine and Tapentadol Hydrochloride with Bovine Serum Albumin (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The in vitro interactions of Famotidine (FT) and Tapentadol hydrochloride (TAP) with bovine serum albumin (BSA) have been studied by fluorescence emission spectroscopy under different conditions. Quenching constants were determined using the Stern-Volmer equation. Two moles FT bound with 1 mole of BSA at 298 K and 3 mole FT bound with 1 mole of BSA at 308 K in presence of TAP. BSA was used for the study as it shows approximately 76% sequence homology to human serum albumin (HSA).Dhaka Univ. J. Pharm. Sci. 15(1): 21-26, 2016 (June)